Carbonyl Activation by Borane Lewis Acid Complexation: Transition States of H2 Splitting at the Activated Carbonyl Carbon Atom in a Lewis Basic Solvent and the Proton‐Transfer Dynamics of the Boroalkoxide Intermediate. Issue 38 (14th June 2017) - Heshmat, Mojgan; Privalov, Timofei
Abstract: By using transition‐state (TS) calculations, we examined how Lewis acid (LA) complexation activates carbonyl compounds in the context of hydrogenation of carbonyl compounds by H2 in Lewis basic (ethereal) solvents containing borane LAs of the type (C6 F5 )3 B. According to our calculations, LA complexation does not activate a ketone sufficiently enough for the direct addition of H2 to the O=C unsaturated bond; but, calculations indicate a possibly facile heterolytic cleavage of H2 at the activated and thus sufficiently Lewis acidic carbonyl carbon atom with the assistance of the Lewis basic solvent (i.e., 1, 4‐dioxane or THF). For the solvent‐assisted H2 splitting at the carbonyl carbon atom of (C6 F5 )3 B adducts with different ketones, a number of TSs are computed and the obtained results are related to insights from experiment. By using the Born–Oppenheimer molecular dynamics with the DFT for electronic structure calculations, the evolution of the (C6 F5 )3 B–alkoxide ionic intermediate and the proton transfer to the alkoxide oxygen atom were investigated. The results indicate a plausible hydrogenation mechanism with a LA, that is, (C6 F5 )3 B, as a catalyst, namely, 1) the step of H2 cleavage that involves a Lewis basic solvent molecule plus the carbonyl carbon atom of thermodynamically stable and experimentally identifiable (C6 F5 )3 B–ketone adducts in which (C6 F5 )3 B is the "Lewis acid promoter", 2) the transfer of the solvent‐bound proton to the oxygen atom of the (C6 F5 )3 B–alkoxide intermediate giving the (C6 F5 )3 B–alcohol adduct, and 3) the SN 2‐style displacement of the alcohol by a ketone or a Lewis basic solvent molecule. Abstract : Activation by complexation : Theory probes the participation of Lewis acid complexation and the resultant catalysis in the hydrogenation of carbonyl compounds by H2 in Lewis basic (ethereal) solvents (see scheme). The results plausibly indicate a novel mechanism.